Kumujan B suppresses TNF-α-induced inflammatory response and alleviates experimental colitis in mice - Li, Xunwei; Di, Qianqian; Li, Xiaoli; Zhao, Xibao; Wu, Han; Xiao, Yue; Tang, Haimei; Huang, Xucan; Chen, Jin; Chen, Shaoying; Gao, Yuli; Gao, Junbo; et al. (Frontiers in Pharmacology, 2024)
Treatments of inflammatory bowel disease (IBD) are diverse, but their efficacy is limited and it is therefore urgent to find better therapies. Controlling mucosal inflammation is a must in IBD drug treatment. The occurrence of anti-tumor necrosis factor α (TNF-α) monoclonal antibodies has provided a safer and more efficacious therapy. However, this kind of treatment still faces failure in form of loss of response. β-Carboline alkaloids own an anti-inflammatory pharmacological activity. While Kumujan B contains β-Carboline, its biological activity still remains unknown. Our data show that Kumujan B attenuated the expression of interleukin 1β (IL-1β) and interleukin 6 (IL-6) induced by TNF-α in mouse peritoneal macrophages. Kumujan B suppressed c-Jun N-terminal protein kinases (JNK) signaling, especially c-Jun for anti-inflammatory response. Furthermore, Kumujan B promoted K11-linked ubiquitination and degradation of c-Jun through the proteasome pathway. In an in vivo study, Kumujan B inhibited the expression of IL-1β, IL-6 and TNF-α and improved the colon barrier function in dextran sulfate sodium salt (DSS)-induced experimental mice colitis. Taken together, Kumujan B exhibited anti-inflammatory effects both in vivo and vitro, which might be a potential therapeutic candidate in treating IBD.